(untitled) (DAPesquisa, 2021)
The advancement of technologies has enabled major evolutions in relation to the development of intelligent machines. To this end, its programming and logic can be understood through the semiotic processes that happen in humans. Through interpretations of signs, machines organize information and make decisions, possessing the ability to learn. In fashion, choice systems are complex because they involve both material and intangible factors. This value system is established at any time in the supply chain and depends specifically on the weights users give for each factor that may vary according to their lifestyle, culture or beliefs. The aim of this paper was to conduct a critical and reflective analysis that discusses the value of the fashion product in users’ lives to the point that they can be chosen by an external and artificial agent. It is believed that considering all levels of circumstances, conditions and factors of use the number of variables in decision making tends to infinity, so it is unlikely that artificial agents can generate value for fashion products in the same way as humans.